Discharge characteristics of plasma sheet actuators - Sosa, Roberto (2007)
The electrical characteristics of a plasma sheet device used for subsonicairﬂow control are studied in this paper. Experiments are undertaken with atwo-wire asymmetrical (different diameters, opposite polarity) electrodeconﬁguration connected to dc high voltage sources in the presence of adielectric plate and under different gases (dry air, nitrogen and oxygen). Forlarge distances electrode-plates it has been found that the discharge currentconsists of a purely dc component. The proximity of the plate reducesnotably this dc current component until a limit situation for which theelectrodes practically lay on the plate and a current pulsed regime issuperimposed on the dc (small) component, thus establishing a plasma sheetregime. This regime could be reached only when the small wire waspositive. This work establishes that the pulsed regime may be associatedwith a succession of positive streamers (cathode directed) which formationis promoted by different parameters of the gas and surface characteristics(thresholds of photoionization and photoemission, charge deposition,...).The dc component seems to be produced by a small number of electronsoriginated in the ionization region of the negative corona that are ampliﬁedin the ionization region of the positive corona. The charged particlesproduced during the streamer propagation could contribute appreciably tothe ion momentum transfer to the gas. This transfer should be due verylikely to the drift of the charged species present in the streamer channelduring the streamer collapsing phase. The source of momentum transferassociated with the dc current would always persist with a magnitude thatdepends on the intensity of this current.